KEY COMPETENCIES FOR THE ROLE OF MARKETING MANAGERS IN ORGANISATIONS - Melaia, Stuart (My University, 2011)
Marketing managers require a set of identifiable competencies in order to effectively perform their roles. The link between competence and organisational competitiveness is established in the strategic marketing literature. The purpose of this research was to identify the key competencies for the role of marketing managers in organisations. The first aim of the research was to identify the key competencies of marketing managers. The second aim was to identify the role of marketing managers in organisations. The final purpose was to explore similarities and differences of perception between organisations and managers regarding the competencies and roles of marketing managers. The investigation was qualitative in nature. Content analysis was performed on a sample of job specifications and interviews with marketing managers. The results were triangulated and compared to the literature. The main finding was that there exist thirty two marketing management competencies that are closely aligned to the role of marketing managers in organisations. The findings were summarised in the form of defined marketing management competencies. The key similarities and differences between organisational and managerial perceptions of marketing management competencies and roles were summarised. The study provides a tool for competency identification, definition and evaluation for marketing educators, practitioners and employers.
MBA - WBS
Keywords: Marketing; Competencies